Urogenital Pain A Clinicians Guide to Diagnosis and Interventional Treatments - Sabia, Michael; Sehdev, Jasjit; Bentley, William; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an up to date, comprehensive, review of the common urogenital painful conditions. It will serve as a valuable resource for clinicians, urologists, surgeons, gynecologists, palliative care physicians, and many other medical providers. The book reviews presenting signs and symptoms, diagnostic workup, differential diagnoses, interventional treatments, and alternative medical therapy for painful conditions that occur in the urogenital region. The text also provides a clear understanding of how pain is transmitted along with what patient populations are at increased risk in suffering these conditions. The risks, benefits, and indications are discussed in detail for the variety of interventional injections that are available to help manage these conditions.
Pelvic Floor Anatomy and Neurovasculature Related to Urogenital Pain -- Ilioinguinal and Genitofemoral Neuralgia -- Myofascial Pelvic Pain -- Sacroiliac Joint Complex Pain -- Piriformis Syndrome and Pudendal Neuralgia -- Lumbar and Sacral Radiculitis -- Scrotal Pain -- Chronic Pelvic Pain of Urogynecologic Origin -- Rehabilitation of the Pelvis and Pelvic Floor -- Cancer Pain in the Urogenital Region -- Spinal Cord Stimulation for Chronic Pelvic Pain -- Intrathecal Drug Delivery Systems -- Psychiatric Aspects in Chronic Pain and Utility of Yoga and Mindfulness Based Cognitive Behavioral Therapy for Pain (Y-MBCT-pain) as a Translational Model -- Complementary and Alternative Medicine.
Keywords: Medicine; Gynecology; Pain medicine; Urology; Medicine & Public Health; Urology; Gynecology; Pain medicine